Implementation of Centralized School Management in Improving Graduate Quality - Agus Sugiono; Nandang Koswara (Journal of Innovation and Research in Primary Education, 2026)
Vocational education quality depends critically on effective management systems aligning educational outputs with industry demands. This study examines Center of Excellence (PK) management implementation in private vocational schools and its impact on graduate quality. A qualitative case study design was employed at SMKS PGRI 35 Jakarta and SMKS Islam Bahagia Jakarta, the only private vocational schools implementing PK programs in West Jakarta 1. Data were collected through semi-structured interviews with 12 key informants, participant observations, and document analysis over four months. Analysis followed systematic qualitative procedures incorporating triangulation to enhance credibility. Findings revealed that systematic PK management through Planning, Organizing, Actuating, and Controlling (POAC) framework significantly enhanced graduate quality. Both schools achieved employment rates of 83% and 79% within three months post-graduation, exceeding the 80% target. Implementation success involved formalized industry partnerships (MoUs with PT Midi Utama Indonesia Tbk and PT Indo Marco Prismata Tbk), curriculum integration with competency certifications (94% and 91% achievement rates), and multilayered supervision systems. Unexpected findings included spontaneous inter-institutional collaboration and student-led peer monitoring mechanisms.  Results support POAC theory's applicability to contemporary vocational contexts while extending understanding of culturally responsive implementation strategies, particularly Islamic values integration. The study demonstrates that resource-constrained private institutions can effectively adapt centralized policies through strategic curriculum design, transparent supervision, and sustained industry engagement to produce competitive graduates.